Funny things a comic strip biography of Charles M. Schulz - Debus, Luca 1994-; Matteuzzi, Francesco 1978- (Top Shelf Productions, 2023)
Discover the man behind Charlie Brown, Snoopy, and the Peanuts gang in this imaginative and tender-hearted tribute told in comic-strip format!
Keywords: Schulz, Charles M. -- 1922-2000; Schulz, Charles M. / (Charles Monroe) / 1922-2000 / Comic books, strips, etc; Cartoonists / Comic books, strips, etc / Biography; Biographical comics; Biographies; Graphic novels; Comics (Graphic works); Comic; Biografie